Racial tension in a "postracial" age - H.W. Wilson Company (Amenia, New York : Grey House Publishing, 2016)
Many Americans would like to believe that because the United States has now twice elected a black president, we live in a "postracial" society where discrimination and racism do not exist or only do among outlying, insignificant extremists. Yet, there has been much in the news to contest this notion-not only in the form of police brutality in black communities but also in persisting residential segregation and social inequities between different populations. In opposition to claims of a postracial society, then, are cries of pervasive structural racism and the rise of such activist groups as Black Lives Matter. We have also seen a resurgence in debates around affirmative action and reparations for slavery. While race may be a "social construct," it still has very real effects on national and global politics and society. This volume will explore the state of race in the United States today. -- Amazon.
1. Race in the media. Racial representation and fictionalization in American media -- Race and beyond: the media's stereotypical portrayals of race / Sam Fulwood III -- Crime coverage in media perpetuates racial stereotypes / Christopher Benson -- Race science rears its ugly head / Gavin Evans -- Why we need to talk about Doc McStuffins and race / Jennifer Harvey -- Rachel Dolezal's story, a study of race and identity, gets "crazier and crazier" / Maria L. La Ganga and Matt Pearce -- Iggy Azalea's post-racial mess: America's oldest race tale, remixed / Britanny Cooper -- Hollywood "race casting": what the industry is getting wrong about diversity / Britt Julious -- Working on the race beat / Jamil Smith -- 2. Health and wealth. The modern American dream -- Why so many minority millennials can't get ahead / Mel Jones -- Tech jobs: minorities have degrees but don't get hired / Elizabeth Weise and Jessica Guynn -- African-Americans are still being victimized by the mortgage market / David Dayen -- Supreme Court's latest race case: housing discrimination / Nikole Hannah-Jones -- More black women are dying from breast cancer than white women -- and the disparity is growing every year / Casey Gueren -- The racial divide within our heart ... attacks / Tom Jacobs -- Racial injustice still rife in health care / Vijay Das and Adam Gaffney -- 3. Criminal justice and racial violence. The fight for equality -- The price of transgression / Gary Younge -- Driving while black / Charles Epp and Steven Maynard-Moody -- The Milwaukee experiment / Jeffrey Toobin -- Terrorism in Charleston / Jelani Cobb -- Unrest in Chicago after police officer charged with murder in shooting of black teenager / Mark Guarino, Wesley Lowery, Mark Berman, and Justin Wm. Moyer -- The steep cost of incarceration on women of color / Tanzina Vega -- 4. In school and on campus. The education race -- The school-to-prison pipeline / Marilyn Elias -- Students see many slights as racial "microaggressions" / Tanzina Vega -- U.S. education: still separate and unequal / Lindsey Cook -- Parents tried to desegregate their schools. The Roberts Court said no. / William Yeomans -- Race, class, or place? / Sam Fulwood III -- Campus police departments struggle with issues of race / Peter Schmidt -- The incidents that led to the University of Missouri's president's resignation / Elahe Izadi -- Yale students and staff are in a huge debate over offensive Halloween costumes / Megan Friedman -- Woodrow Wilson's legacy gets complicated / Jennifer Schuessler -- 5. A new civil rights movement and current perspectives on race. A new era of civil rights challenges -- Growing up "post racial," teens suddenly find a world that isn't / Greg Toppo -- America's "postracial" fantasy / Anna Holmes -- Will today's hispanics be tomorrow's whites? / Jamelle Bouie -- The witnesses / Jay Caspian Kang -- Head of hispanic advocacy group: Trump's remarks racist / Gabriel Debenedetti -- The rebirth of black rage / Mychal Denzel Smith -- A different take on race / Joseph P. Williams -- For black millennials, a determined hope tempered by frustration / Henry Gass -- The truth about the white working class: why it's really allergic to voting for Democrats / Sean McElwee.
Includes bibliographical references (pages 189-194) and index.
Keywords: Racism -- United States -- History -- 21st century -- Sources; Post-racialism -- United States -- History -- 21st century -- Sources; Equality -- United States -- History -- 21st century -- Sources